Precision or adaptability? Contrasting effects of linear and non-linear pedagogy models in handball instruction - Espoz-Lazo, Sebastián; Rahmati Arani, Masoud; Hinojosa-Torres, Claudio; Farías-Valenzuela, Claudio; Dehghani Zadeh, Jalal (Frontiers in Sports and Active Living, 2025)
IntroductionResearch in physical education increasingly compares linear and non-linear teaching for invasion games. The present study examined how these frameworks affect technical execution and game-based decision-making in handball.MethodsA quasi-experimental pretest–posttest study (5 weeks) assigned students to a Linear model (progressive, repetitive practice) or to Non-Linear Pedagogy (ecological dynamics, task representativeness). Technical skills were measured with the Zinn Handball Skills Battery and the Johanson Ability Test; tactical performance with the Game Performance Assessment Instrument in representative scenarios. Inter-rater reliability was established among independent observers.ResultsBoth groups improved technical execution from pre- to post-test. The Linear group showed greater gains in precision-based tasks (passing, shooting), whereas the Non-Linear group improved more in tactical dimensions (decision-making, off-the-ball support). ANOVA indicated significant main effects of time but no group × time interaction; intra- and inter-group contrasts revealed differentiated developmental patterns.DiscussionFindings suggest complementary strengths: linear instruction favors technical refinement, whereas non-linear approaches promote adaptability, perception–action coupling, and context-sensitive responses.ConclusionEducators should adopt flexible, learner-centred programming integrating both models to align with learners' developmental needs.